Study of Isotherm and Kinetics for Remediation of Congo Red Using Nanocomposite Bead - Sarkar, Pankaj; Sarkar, Swagatam; Santra, Dhiman; Denrah, Shanku; Sarkar, Mitali (Fine Chemical Engineering, 2022)
Cellulose-based nanocomposite (FeCNB) has been synthesized via sol-gel conversion for adsorptive remediation of Congo red, a carcinogenic and mutagenic azo dye, from water. The bead was characterized by Fourier transform infrared (FT-IR), scanning electron microscopy (SEM), field emission scanning electron microscopy (FESEM), energy dispersive X-ray analysis (EDAX) and transmission electron microscopy (TEM). The effect of adsorbent dose, pH, contact time, shaking speed, initial dye concentration and temperature was carried out in a batch adsorption study. The maximum removal of Congo red was found at pH 6.0, corresponding to the adsorbent dose of 1.0 gdm-3 and 90 min of contact time. The experimental data were analyzed using different isotherm and kinetic models. The data was fitted best to Langmuir isotherm model and pseudo-second-order kinetic model. The maximum adsorption capacity evaluated from Langmuir isotherm is 3.52 mgg-1 at 303 K. Thermodynamic study was carried out to evaluate the changes in Gibbs free energy (ΔG0 ), enthalpy (ΔH0 ) and entropy (ΔS0 ) of the dye-adsorbent interaction. The negative ΔG0 values at all temperatures suggested the spontaneous nature; the positive ΔH0 value indicated the endothermic nature and the positive ΔS0 indicated the increased randomness of the adsorption process. Desorption study found 0.1 (M) NaOH as the most suitable eluting agent for dye-loaded adsorbent. The adsorbent can be used up to five successive cycles of adsorption-desorption.